2022
DOI: 10.3390/cancers14215325
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Immunotherapy for Patients with Head and Neck Cutaneous Squamous Cell Carcinoma

Abstract: Cutaneous squamous cell carcinoma (CSCC) is the second most common non-melanoma skin cancer. A majority of patients present with localized disease, but some can present with locally advanced or metastatic disease. Most of these advanced cases occur in the anatomical head and neck region and are associated with more aggressive disease, necessitating prompt and effective treatment. Prior to the emergence of immunotherapy, systemic treatment options were limited to platinum-based chemotherapy and salvaged with ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…In addition, the treatment choice for SLNB-positive patients is still a matter of debate. Furthermore, novel drugs have been rapidly emerging for treatment of not only melanoma but also nonmelanoma skin cancers [ 139 , 140 ]. Therefore, further, high-quality studies including randomized clinical trials in accordance with these novel drugs are necessary to determine the significance of SLNB for prognosis and appropriate methods or treatment according to the SLN status in skin cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the treatment choice for SLNB-positive patients is still a matter of debate. Furthermore, novel drugs have been rapidly emerging for treatment of not only melanoma but also nonmelanoma skin cancers [ 139 , 140 ]. Therefore, further, high-quality studies including randomized clinical trials in accordance with these novel drugs are necessary to determine the significance of SLNB for prognosis and appropriate methods or treatment according to the SLN status in skin cancer.…”
Section: Discussionmentioning
confidence: 99%
“…One randomized trial including a cisplatin‐based regimen showed an ORR of 34% 22–24 . The major disadvantages of these cytotoxic regimens are low clinical efficacy with a short response duration and increased toxicity 25 . Likewise, several types of EGFR inhibitors have been prospectively investigated but have shown equivalent clinical efficacies compared with cytotoxic regimens.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] The major disadvantages of these cytotoxic regimens are low clinical efficacy with a short response duration and increased toxicity. 25 Likewise, several types of EGFR inhibitors have been prospectively investigated but have shown equivalent clinical efficacies compared with cytotoxic regimens. First, the efficacy of cetuximab was investigated in a phase II study, demonstrating an ORR of 28%.…”
Section: Discussionmentioning
confidence: 99%